IMPLEMENTATION SMOKE FREE AREA (SFA) FACULTY OF HEALTH SCIENCE (FHS) MUHAMMADIYAH UNIVERSITY OF SURAKARTA FOR REDUCE NON COMMUNACABLE DISEASE PREVALENCE - Nugroho, Purwo Setiyo; Kusumawati, Yuli; Wijayanti, Anisa Catur (Krafon Publishing, 2019)
Introduction: The implementation of SFA in Faculty of Health Science, it is influenced by the basic knowledge about health. Implementation of SFA has not been optimal, because the results of the preliminary survey show that 11% of students and employees of Health Science Faculty, have ever smoked and 89% have not ever smoked in surrounding its area, since the Dean?s provision was determined in 2007. The purposes of this research are to know supporting factors and inhibitor factors that influence the application of SFA. Methods: The research method uses a qualitative approach with phenomenology and the number of informants in this reserach were 6 (six) people, namely lecturer?s of UMS and students of organization Health Science Faculty. Informants were determined by purposive sampling method, and data were collected by using semistructured interview techniques. Result: Finally, the results of this research revealed that the Faculty of Health Science has Decree?s Dean about SFA, the punishment of warning for smokers in SFA?s of Faculty of Health Science, UMS has a stop-smoking clinic and it has sponsor as supporting factor for SFA in Faculty of Health Science UMS. The inhibitor factors of SFA?s are lack of socialization, lack of education, stop-smoking clinic has not been maximized, many people still smoke in this faculty and the absence of a special task force of anti-smoking.